2014
DOI: 10.1097/tp.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein-27 Delays Acute Rejection After Cardiac Transplantation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Similarly, genetic overexpression of HSPs in the donor organ can alter alloimmunity in the context of experimental heart transplantation. Specifically, hearts transplanted from transgenic mice overexpressing HSP27 experienced a delayed onset of acute rejection and reduced IRI-induced apoptosis as compared with HSP27-negative hearts from littermate controls (102). A potential mechanism to explain these observations is innate immune-driven immunological memory occurring as a result of epigenetic reprogramming after stimulation.…”
Section: Implications For Damps In Sot Therapiesmentioning
confidence: 98%
“…Similarly, genetic overexpression of HSPs in the donor organ can alter alloimmunity in the context of experimental heart transplantation. Specifically, hearts transplanted from transgenic mice overexpressing HSP27 experienced a delayed onset of acute rejection and reduced IRI-induced apoptosis as compared with HSP27-negative hearts from littermate controls (102). A potential mechanism to explain these observations is innate immune-driven immunological memory occurring as a result of epigenetic reprogramming after stimulation.…”
Section: Implications For Damps In Sot Therapiesmentioning
confidence: 98%
“…Increased levels of Hsps in transplant organ cells either by treatment or genetic manipulation have been demonstrated to be beneficial for transplant longevity ( 16 ). Hsps promote refolding of proteins denatured due to IRI, protecting cells from IRI-induced death.…”
Section: Intracellular Hsps Protect Allografts From Ischemia–reperfusmentioning
confidence: 99%
“…Hsps’ cytoprotective capacity was also demonstrated in organs that were genetically modified to overexpress these proteins. Hearts from mice overexpressing Hsp27 induction correlated with increased survival when transplanted in fully MHC-mismatched hosts ( 16 ). These hearts presented reduced caspase activation after subjection of ischemic/reperfusion conditions.…”
Section: Intracellular Hsps Protect Allografts From Ischemia–reperfusmentioning
confidence: 99%
“…It has also be reported that overexpression of HSP27 in mouse hearts delays the allograft rejection by inhibiting the tissue damage. Indeed, the presence of HSPs and HSP specific lymphocytes are not always indicative of a deleterious response, they might reflect an anti-inflammatory protective response also [ 45 , 46 ].…”
Section: Hsp In Transplantationmentioning
confidence: 99%